Three variants of immune responses to balneotherapy at the spa Truskavets’ in patients with chronic pyelonephritis and cholecystitis - Kul’chyns’kyi, Andriy B; Zukow, Walery (Journal of Education, Health and Sport, 2018)
Background.The results of research the influence of balneotherapy in the spa Truskavets’ on the immune status of the organism are ambiguous. This may be due to the differences between the cohorts of the subjects under investigation, and individual immune reactivity. Therefore, research in this direction remains relevant. The purpose of this study is to identify variants of the immunotropic effect of balneotherapy.Material and methods. Inbasalconditionsin33 men and 10 womenwithchronicpyelonephritisandcholecystitisinremission, werecordedtwice, before and after balneotherapy at the spa Truskavets’, parameters of Immune status on a set of I and II levels recommended by the WHO.Results. Three variants of immune responses to balneotherapy have been revealed.In 46,5% of patients changes in immune parameters fluctuated around the zero line and did not go beyond the limits of one Z-unit, that is, there was a quasi-zero immunotropic effect. In 32,6% of patients, moderate activation of neutrophil bactericidal activity was detected against as Staph. aur., and E. coli, an increase in the level of immunoglobulins G and M, as well as T-helpers, while the level of cytolytic T-lymphocytes was moderately reduced, in the absence of significant changes in the remaining 5 parameters of the immunogram. In 20,9% of patients, on the contrary, the level of T-killers has moderately increased, as well as the level of natural killers, in combination with a significant increase in neutrophil bactericidity against gram-positive and gram-negative bacteria, in the absence of significant changes in the remaining 7 parameters of the immunogram.Conclusion. Immune responses to balneotherapy have a polyvariant nature, which is probably due to individual reactivity, and will be the subject of the next study.